HOW DO ISLAMIC BANKING STAKEHOLDERS INTERPRET THE ETHICAL AND SHARIA IMPLICATIONS OF ARTIFICIAL INTELLIGENCE ADOPTION? A QUALITATIVE STUDY IN INDONESIA - Imam Arif Murfih Ali Moch Ridho; Zulfikar Hasan (CV. Visionary Raya Sakti, 2026)
The integration of artificial intelligence (AI) within Islamic banking is accelerating, yet its ethical and Sharia implications remain insufficiently understood. This study explores how key Islamic banking stakeholders in Indonesia— including regulators, Sharia Supervisory Board (SSB) members, Islamic bank executives, fintech developers, and ethics scholars—interpret the moral, regulatory, and jurisprudential meaning of AI adoption. Adopting an interpretivist qualitative design, data were collected through semi-structured interviews and analyzed using NVivo through open, axial, and selective coding. The findings reveal three interrelated themes: (1) AI is perceived as a strategic enabler of efficiency, financial inclusion, and institutional competitiveness; (2) ethical and Sharia ambiguities emerge in areas related to algorithmic intention, explainability, fairness, bias, and the legitimacy of machine-based decision-making; and (3) trust and governance are central to acceptance, with stakeholders expecting continuous oversight, transparency, and alignment with maqāṣid al-sharīʿah. The study concludes that AI adoption in Islamic banking requires more than technological readiness—it necessitates a tailored responsible AI governance model grounded in Islamic jurisprudence. The research contributes to emerging discourse on Islamic digital ethics and offers actionable implications for regulation, Sharia governance, and responsible AI implementation.